Optimal operation of a parabolic solar collector with twisted-tape insert by multi-objective genetic algorithms - Borunda, Mónica; Garduno-Ramirez, Raul; Jaramillo, O.A. (Renewable energy, 2019)
Nowadays, concentrated solar energy is a promising renewable heat source. Specifically, parabolic trough collectors are an attractive technology to produce solar heat for high and low enthalpy processes. One way to improve these devices is to increase the heat transfer by placing inserts in the receiver tube. We analyze the performance of a parabolic trough collector with a twisted tape insert by reformulating the efficiencies and enhancements in terms of 1st and 2nd Laws of Thermodynamics as polynomial approximations of the main process variables, mass flow of the heat transfer fluid and twist ratio of the tape insert. This approach allow to state an optimization problem, solved with multi-objective genetic algorithms, to find out the best main process variables for the best operation conditions of the collector. As a result, the best, and worst, Pareto-optimal solutions correspond to small, and large, twist ratios. Moreover, the collector's efficiency is higher for small mass flow but the enhancement is smaller. On the other hand, the collector's efficiency is smaller for large mass flow but the enhancement is higher. These results provide an operating strategy for the twist ratio and mass flow depending on the requirements of the application process.